Ab-initio Molecular Orbital and DFT Studies on the Effect of Methyl Group Perturbations in Isoxazoles and Thiazoles - Kumar, Alok; Tripathi, Sarita; Yadav, B.P. (Asian Journal of Chemistry, 2010)
The effect of methyl group substitution in isoxazoles and thiazoles have been studied by abinitio and density functional methods. In the present work, the calculated values, namely, net charges, dipole moment, ionization potential, electron-affinity and heat of formation are reported and discussed in terms of the reactivity of isoxazole systems.